Major oxide, Sr, Zr, and isotopic composition of rocks and sediments from western Greenland - Martin, Jonathan; Martin, Ellen; Deuerling, Kelly (IEDA: EarthChem Library, 2017)
Abstract: Major oxide, Sr, Zr, and isotopic composition of bedload sediments, suspended sediments, moraine sediments, and rocks along a ~170 km transect from the Greenland Ice Sheet near Kangerlussuaq to the coast at Sisimiut in western Greenland. Other Description: Scribner CA, Martin EE, Martin JB, Deuerling KM, Collazo DF, Marshall AT (2015) "Geochimica et Cosmochimica Acta" 170: 157-172